1995
DOI: 10.1002/ajh.2830490411
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug transporter p‐glycoprotein 170 as a differentiation antigen on normal human lymphocytes and thymocytes: Modulation with differentiation stage and during aging

Abstract: P-glycoprotein 170 (P-gp), the multidrug transport pump, excludes drugs from the interior of cells and is inhibited by agents such as cyclosporin A (CsA), verapamil, and FK-506, which are also substrates for the P-gp pump. This work documents the age- and differentiation-related changes in P-gp on T and B lymphocytes from human blood or spleen, and its absence on most thymus and bone marrow cells. Analysis of rhodamine 123 (Rh123) dye efflux, and its inhibition by cyclosporin A, was used as a quantitative meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
47
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 60 publications
16
47
1
Order By: Relevance
“…Activated T lymphocytes demonstrated preferential accumulation and retention of the TH9402 rhodamine derivative over resting T cells. Indeed, we found that resting T lymphocytes, which express MDR1, 29 extruded TH9402 through this channel transporter, whereas the cellular activation process led to an impairment in MDR1-mediated TH9402 efflux. These kinetics of accumulation of TH9402 have resulted in the photodynamic eradication of responder cells immunized ex vivo against stimulator cells, in conditions simulating MHC-mismatched transplantation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Activated T lymphocytes demonstrated preferential accumulation and retention of the TH9402 rhodamine derivative over resting T cells. Indeed, we found that resting T lymphocytes, which express MDR1, 29 extruded TH9402 through this channel transporter, whereas the cellular activation process led to an impairment in MDR1-mediated TH9402 efflux. These kinetics of accumulation of TH9402 have resulted in the photodynamic eradication of responder cells immunized ex vivo against stimulator cells, in conditions simulating MHC-mismatched transplantation.…”
Section: Discussionmentioning
confidence: 95%
“…26 Pgp, the product of the multidrug-resistance-1 (MDR1) gene, is a protein expressed not only in normal stem cells, but also in T lymphocytes. [27][28][29][30] Investigators have proposed that T-cell activation may actually lead to the inactivation of Pgp. 29 Thus, activated T cells should fail to extrude rhodamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No toxicity was seen at concentrations up to 250 M, and PBMC were at least 500-fold less susceptible to the endoperoxides, thus demonstrating the selective cytotoxic properties of endoperoxide compounds against rapidly dividing cell lines. An IC 50 value for doxorubicin in PBMC could not be determined because of large inter-individual variations in IC 50 values, possibly arising from polymorphic expression of the efflux pump p-glycoprotein in PBMC (50), of which doxorubicin is known to be a substrate (51). The deoxygenated counterpart of PFDHA, dPFDHA, which has an ether linkage in place of the endoperoxide bridge, displayed low levels of cytotoxicity; IC 50 values were 50-and 130-fold higher in HL-60 and Jurkat cells, respectively, than for the parent compound, thus confirming that high levels of cytotoxic activity are dependent upon the presence of the endoperoxide bridge.…”
Section: Lc-ms Analysis and Quantification Of Intracellular Endoperoxidementioning
confidence: 99%
“…These transport proteins play a critical role in the absorption, distribution, metabolism and excretion of drugs and toxins. 4 Moreover, these proteins were described in thymocytes, [5][6][7] mature lymphocytes, 8,9 dendritic cells, 10,11 monocytes 12 and macrophages. 13 It has been suggested that multidrug transporters may play a role in the cells of the immune system, mediating the efflux of xenobiotics 14,15 and regulating cell activation [16][17][18] and migration.…”
mentioning
confidence: 99%